A comparison of pump-controlled retrograde trial off to arterio-venous bridging for weaning from venoarterial extracorporeal membrane oxygenation. (29th January 2019) - Pandya, Nischal R; Daley, Michael; Mattke, Adrian; Shikata, Fumiaki; Betts, Kim; Haisz, Emma; Black, Anthony; Anderson, Benjamin; Alphonso, Nelson; Venugopal, Prem
Abstract: OBJECTIVES: The aim of the study is to compare a technique of pump-controlled retrograde trial off (PCRTO) to insertion of an arterio-venous (AV) bridge to conduct a trial from venoarterial extracorporeal membrane oxygenation (VA ECMO). METHODS: We studied all patients who were weaned from VA ECMO using either PCRTO or AV bridging from November 2014 to April 2018. Demographic data, indications for ECMO, duration of ECMO, duration of trial period off ECMO and survival were compared between the 2 groups. RESULTS: Seventy-nine patients were placed on VA ECMO from November 2014 to April 2018, of whom, 51 (65%) patients met the study inclusion criteria: 31 (61%) patients who had a trial period from VA ECMO using PCRTO and 20 (39%) patients who were weaned using an AV bridge. The indications for ECMO included cardiac ( n = 16 and 11, respectively) and non-cardiac aetiologies ( n = 15 and 9, respectively). There was 1 death in each group. The duration of the trial off VA ECMO was significantly shorter in the PCRTO group (median = 88.0 vs 196.6 min, P < 0.001). There were 2 conversions from PCRTO to AV bridging during the trial period off ECMO (2.9-kg neonate following a Norwood procedure and 2.2-kg patient following repair of ectopia cordis). CONCLUSIONS: PCRTO is a safe, simple and reproducible approach for enabling a trial period while preserving the circuit during weaning from VA ECMO. In our study, the duration of the trial period off VA ECMO was significantly shorter in the PCRTO group. PCRTO avoids manipulation of the ECMO circuit, provides a 'stress test' to evaluate cardiorespiratory reserve during the trial period off ECMO, is applicable for a wide variety of cardiac and non-cardiac indications and facilitates multiple attempts at weaning from ECMO.